Health workers' manual on counselling for maternal and child health. (Manila World Health Organization, Regional Office for the Western Pacific, 1995)
Presents substantial information on educating and counseling people to promote healthy behavior among pregnant women and those who have children under the age of five. Provides step-by-step procedures on specific maternal and child health situations. A very useful manual for those who are pregnant, planning to have a baby and for those who have children under five years of age. Uses simple and straightforward words for easy understanding.
This is intended to help managers of health services to ensure that good quality Maternal and Child Health/Family Planning (MCH/FP) care is provided to all in need of such care. The manual uses practical ideas on how to better plan, implement and evaluate MCH/FP programs through strategies, objectives and procedures.
Keywords: Maternal health services -- Handbooks, manuals, etc; Child health services -- Handbooks, manuals, etc; Health counseling -- Handbooks, manuals, etc